Identification of Protein Nitrosothiols Using Phosphine-Mediated Selective Reduction - Li, Sheng (2011)
Regulation of protein function by S-nitrosation of critical cysteines is known to be an important mechanism for nitric oxide signaling. Evidence for this comes from several different experimental approaches including the ascorbate-based biotin switch method. However technical problems with specificity and sensitivity of ascorbate reduction of S-nitrosothiols limit its usefulness and reliability. In the current study we report the use of triphenylphosphine ester derivatives to selectively reduce SNO bonds in proteins. After triphenylphosphine ester reduction thiols were tagged with biotin or fluorescently labeled maleimide reagents. Importantly we demonstrate that these compounds are specific reductants of SNO in complex biological samples and do not reduce protein disulfides or protein thiols modified by hydrogen peroxide. Reduction proceeds efficiently in cell extracts and in whole fixed cells. Application of this approach allowed us to demonstrate S-nitrosation of specific cellular proteins, label S-nitrosoproteins in whole fixed cells (especially the nuclear compartment) and demonstrate S-nitrosoprotein formation in cells expressing inducible nitric oxide synthase.